MASALAH IMIGRAN GELAP DALAM HUBUNGAN AMERIKA SERIKAT DAN MEKSIKO - Mega Wahyu Purnomo (2011)

(untitled)
Migration is a global phenomenon caused not only by economic factor but many others like social, political, cultural, environmental, health, education, etc. It generally takes place from the area of less economic opportunities and retarded social development towards developed and fast developing area. Illegal immigration into the United States is a highly profitable proposition for both employers and the United States government, and it also benefits Mexico, which is the largest source country o